Kajian Biaya Dan Waktu Perjalanan Angkutan Kargo Menuju Bandar Udara Soekarno-Hatta - Subekti, Sitti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
Air transport cargo seniice is a form of air trn11sportation sector so as to passengers transport. TI1e mai11 and s1qrporti11g ai111ort facilities 11eeded to se11Je the needs of the users. Cargo air has been used as motivation factor level competitive business currently and become an important factor for tl1e process of s11pply chain i11 111a11y kinds of industrial activity. T1ie research using primary and seco11dar 1 data.TI1ere ·were 31 respondents participated as samples which consist of private cargo and companies cargo on domestic airport cargo ten11i11al of Soekanw-Hatta. Quantitive descriptive inethod was used to anqlyze the data with the application of MS Excell. T11e result of the study shows that a cargo transport travel expenses to Soekarno-Hatta Airport is Rp 100,000 to 200,000,. The average length of time of travel toward SoekarnoHattais between 1-2 hours.Key Words: air transport cargo service, airport, travel expenses, length of time of travel